Mediating Healthcare Communication in Nigeria: Chatbot Technologies and Doctor–Patient Engagement - Chinelo Ebele Uchendu; Timothy Ekeledirichukwu Onyejelem; Omolara Oluwabusayo Akin-Odukoya (Matondang Journal, 2026)
The Nigerian healthcare system continues to face persistent communication challenges arising from high patient-doctor ratios, time constraints, infrastructural deficits, and uneven access to medical information, particularly in underserved and rural communities. Within this context, digital health innovations, especially chatbot technologies are increasingly positioned as mediating tools capable of enhancing healthcare communication and supporting doctor-patient engagement. This study examines how chatbot-powered applications function as intermediaries in healthcare communication in Nigeria, focusing on their roles in information dissemination, patient education, preliminary consultation, and follow-up interaction. Based on the existing studies, Internet materials and journal publications, the paper explores the extent to which chatbots influence accessibility, clarity, responsiveness, and trust in doctor-patient interactions. The paper argues that chatbots significantly improve access to basic health information, reduce communication bottlenecks, and empower patients to engage more actively in their healthcare decisions. However, challenges related to language diversity, digital literacy, cultural sensitivity, data privacy, and the perceived absence of human empathy limit their full communicative potential. The paper concludes that while chatbot technologies cannot replace face-to-face medical consultations, they serve as critical complementary tools for mediating healthcare communication in Nigeria. It recommends context-sensitive design, regulatory oversight, and integration into broader health communication strategies to maximize their developmental and public health impact.